Strategiczne znaczenie tworzenia przewagi konkurencyjnej w handlu żywnością na przykładzie wybranych dużych sieci handlowych - analiza i ocena - Michałowska, Mariola (Strategic Importance of Competitive Advantage Creation in Food Trade on the Example of the Chosen Large Food-Trading Companies - Analysis and Evaluation, 2005)
Currently large food-trading companies are facing a difficult task of building permanent competitive advantage, as well as of adjusting their actions to needs and expectations of their clients. Due to quick development of large food-trading companies, in order to be successful one has to "stand out". In accordance with the dictum "stand out, or die" permanent lowering the unit cost without lowering quality, and creating a bond with ones' clients (and gaining new ones) by means of prices lower than competition, proves to be a successful strategy of gaining competitive advantage in food trade.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 80-84